Operational investments in R&D as a strategy for differentiated performance - Esteves, Henrique Suathê; Pessanha, José Francisco Moreira; Cardoso, Ricardo Lopes; Viana, Renata Kaori Tani (Advances in Scientific and Applied Accounting, 2023)
Objective: To analyze the contribution of operational investment strategies focused on R&D to the generation of distinguished returns compared to strategies focused on Capex. Method: Based on the Fama and French’s 3, 5 and 6-factor models, the generation of distinguished returns was measured through the abnormal returns of portfolios sorted to segregate stocks by size and R&D or Capex levels. Results: There was no significant relationship between Capex levels and an increase in abnormal returns. In portfolios sorted by R&D, a significant relationship was observed between R&D levels and an increase in abnormal returns for microcaps and smallcaps, regardless of the model used. It was also found that the generation of abnormal returns by microcaps with high R&D investments does not depend on the level of investments in Capex. Contribution: The literature has rejected the existence of abnormal returns of aggressive R&D firms in value-weighted portfolios. This study innovates in the way portfolios are sorted, showing that the relationship between abnormal returns and R&D comes mainly from low market value stocks, even with the use of weighted returns, and that such relationship is considered robust by the main pricing models currently in use. With its findings, this research provides theoretical and empirical support to academia and accounting standard-setting bodies, demonstrating the value relevance of R&D investments. In addition, this study contributes to society and the market by potentially helping companies and shareholders to allocate their resources efficiently.